2021
DOI: 10.1111/sms.14112
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of aquatic exercise in adults with and without chronic disease—A systematic review with meta‐analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 77 publications
1
23
0
2
Order By: Relevance
“…Interestingly, it also suggests that Aqua walking might have a greater effect on the quality of life and health perception in aging people compared to a land-based walking practice such as Nordic Walking. These results are in line with several previously published results highlighting a similar-to-greater impact of regular aquatic-based immersed physical activities on both functional and psychological health and well-being in aging individuals [9][10][11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, it also suggests that Aqua walking might have a greater effect on the quality of life and health perception in aging people compared to a land-based walking practice such as Nordic Walking. These results are in line with several previously published results highlighting a similar-to-greater impact of regular aquatic-based immersed physical activities on both functional and psychological health and well-being in aging individuals [9][10][11].…”
Section: Discussionsupporting
confidence: 93%
“…Due to its thermic and mechanical properties, water-immersed exercise has been encouraged, particularly in individuals facing functional impairments [ 7 ], and such aquatic activities using the properties of water such as density, hydrostatic pressure and buoyancy [ 8 ] keep gaining in popularity. While aquatic-exercise modalities such as water-aerobic or aqua-biking are today frequently practiced in the general population, some clinical water-based rehabilitation programs have specfically been developed and found effective in patients with chronic diseases [ 9 ]. In their work, Siqueira Andrade and collaborators for instance showed that 12 weeks of both aerobic and resistance water training, performed twice a week, had the ability to improve functional capacities while maintaining the quality of life perception among 64.3 year-old women (±3.1 years) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This sport has many benefits in accordance with the results of the meta-analysis of Faíl et al, (2022), Water sports are increasingly recommended for healthy individuals or with special health conditions, water-based training is found to benefit strength, balance and cardiorespiratory fitness, disease Bones such as pain, balance, flexibility, and strength are also beneficial in conditions of hypertension, stroke, diabetes, multiple sclerosis, and Parkinson's disease. This sport can improve health and physical fitness in both healthy people and those with chronic diseases.…”
Section: Discussionmentioning
confidence: 66%
“…Both obtained significant results for the assessments with UPDRS-III, BBS, the ABC scale, TUG and FES, and postural alterations in the sagital and coronal planes. Other authors have indicated that hydrotherapy could be a safe and effective alternative for patients with problems in the axial axis and chronic diseases [ 59 ].…”
Section: Discussionmentioning
confidence: 99%